ANALISIS PASSING JARAK PENDEK TIM FUTSAL SMK BATIK 02 SURAKARTA - Saputro, Muhammad Ryan Mardyanto; Warthadi, Anugrah Nur; Fatoni, Muhad (Jurnal Porkes, 2024)
The problem in this study is that the achievement of the futsal team of SMK Batik 02 Surakarta is still low in the match and in the championship is still very minimal and the passing ability of students is still low. The purpose of this research is to examine how the passing training program is able to provide good student passing learning outcomes. This research method uses descriptive quantitative. The subjects of this study were 15 male futsal team players. Data collection techniques were obtained through direct observation in a 30-minute futsal match and a 10-minute break and each player passed 15 times. With the results of the average value of 17.47 the middle value is 17.00 Standard Deviation 2.06, while the lowest passing score is 15 and the highest passing score is 20. The category “less” with a percentage of 0% (0 people), the category “enough” with a percentage of 40% (6 people), the category “Good” with a percentage of 33.3% (5 people) and the category “very good” with a percentage of 26.7% (4 people). The conclusion is that the passing test results are quite good with the lowest passing result of 15 times and the highest is 20 times.